Size effect of axial-loaded concrete-filled steel tubular columns with different confinement coefficients. (1st November 2019) - Jin, Liu; Fan, Lingling; Li, Ping; Du, Xiuli
Highlights: The size effect of circular/square CFST columns is explored using a 3D meso-scale numerical method. As the confinement coefficient increases, the size effect in the nominal compressive strength is gradually weakened. A theoretical formula considering the size effect was established. Abstract: Numerous size effect laws of concrete materials have been proposed by scholars, while the size effect laws for concrete filled steel tubular members are still under study. A three-dimensional meso-scale numerical model that can consider the heterogeneities of concrete and concrete-steel tube interactions was established to study the size effect in concrete filled steel tubular columns. The failure behavior of axial-loaded circular/square concrete filled steel tubular columns having different structural sizes under different lateral constraints (represented by confinement coefficients) were investigated based on the meso-scale method. The influence of lateral confinement on nominal axial compressive strength for concrete columns and corresponding size effect were also explored. As the simulation results indicating, with increasing the specimen size, the nominal axial compressive strength decreases, and size effect is weakened as the confinement coefficient increases. Moreover, combining with the influencing mechanism of steel tube on compressive strength for axial-loaded concrete column, a theoretical formula that can describe the influence of lateral constraint on size effect was established according to the available size effect law for concrete materials. Comparing with the simulation results and reliable test data, the accuracy and rationality of the theoretical formula is well verified.